2013
DOI: 10.1007/s10608-013-9561-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Change Across Cognitive-Behavioral and Light Therapy Treatments for Seasonal Affective Disorder: What Accounts for Clinical Status the Next Winter?

Abstract: Efficacious treatments for seasonal affective disorder include light therapy and a seasonal affective disorder-tailored form of cognitive-behavioral therapy. Using data from a parent clinical trial, these secondary analyses examined the relationship between cognitive change over treatment with cognitive-behavioral therapy, light therapy, or combination treatment and mood outcomes the next winter. Sixty-nine participants were randomly assigned to 6-weeks of cognitive-behavioral therapy, light therapy, or combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…As a way of integrating these seemingly disparate findings, it may be that the measurement of self-reported cognitive change in CBTs captures change in cognitive vulnerabilities whereas in treatment with somatic therapies, measurements of cognitive change capture the deactivation of state-dependent negative cognitions. (For a similar argument, see Evans et al, 2013). This hypothesis is endorsed by Garratt et al (2007), who conclude that "evidence suggests that cognitive changes associated with pharmacotherapy are more superficial than those associated with cognitive therapy" (p. 224).…”
Section: Linksmentioning
confidence: 96%
See 3 more Smart Citations
“…As a way of integrating these seemingly disparate findings, it may be that the measurement of self-reported cognitive change in CBTs captures change in cognitive vulnerabilities whereas in treatment with somatic therapies, measurements of cognitive change capture the deactivation of state-dependent negative cognitions. (For a similar argument, see Evans et al, 2013). This hypothesis is endorsed by Garratt et al (2007), who conclude that "evidence suggests that cognitive changes associated with pharmacotherapy are more superficial than those associated with cognitive therapy" (p. 224).…”
Section: Linksmentioning
confidence: 96%
“…Quilty, McBride, and Bagby (2008) reached a similar conclusion from an investigation in which they used structural equation modeling to characterize pre-to post-treatment changes in cognitions and symptoms, although cognitive change and symptom change was measured concurrently. In a study of seasonal affective depression, Evans et al (2013) reported that in CBT, but not in light therapy, cognitive changes during 6 weeks of treatment predicted depressive symptoms at 1-year winter follow-up. In contrast to the three studies just cited, each of which found specificity in the relation between cognitive change and symptom change, Segal and colleagues reported that cognitive reactivity predicted depressive relapse irrespective of whether it followed from treatment with CT or antidepressant medications (Segal et al, 1999(Segal et al, , 2006.…”
Section: Cognitive Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Bright light therapy (BLT), also called phototherapy, refers to the use of glare therapy to treat depressive symptoms [24], BLT was originally used to treat patients with seasonal affective disorder [25][26][27][28][29]. Numerous studies indicate direct and indirect effects of light on mood.…”
Section: Introductionmentioning
confidence: 99%